Professional Challenges Faced by Physical Education Teachers in Completing Their Daily Lessons from Other Academic Subjects - Saleh , Ayhem; Majid , Saud (Journal of Physical Education, 2025)
This study aims to identify the professional challenges faced by physical education teachers in completing their teaching assignments (sports education lessons) due to the inclusion of other academic subjects in schools affiliated with the General Directorate of Education in Nineveh. The researchers adopted a descriptive methodology, covering a research sample of 317 male and female physical education teachers in Nineveh’s schools. Appropriate scientific procedures and statistical methods were employed. The findings indicate that physical education teachers are highly aware of the significance of the professional challenges they face, showing closely related arithmetic averages. The professional challenges identified by the researchers are equally significant for male and female teachers.